Didactic Modeling in Teaching Students Pedagogues (International Journal of Scientific Research and Management (IJSRM), 2018)
This article is a theoretical study on a model of higher education education at Thracian University, Faculty of Pedagogy in Bulgaria. The teaching process in the subject "Primary School Pedagogy" is being subjected to didactic study in student pedagogues. Theoretically, the methods by which the teachers interact with the students are studied. In their understanding, the interactive lecture in the academic environment is much more successful. The article follows the steps of modeling a didactic matrix in its entirety. There is a need for special didactic modeling from the position of the different topics and from the position of the learning activities with understanding and experience. He argues that didactic modeling evolves into a specially organized simulation-based learning environment. Thus, once, it modeled the learning environment and the second time: a simulation environment was modeled specifically for it. The unique in this process of learning is that it is led by two professors - associate professor and professor. The planned training takes the form of dialogue in front of the students they are involved in. In developing academic lectures, teachers define educational goals, construct training materials, and evaluate how the didactic model is constructed. The didactic model is flexible and adaptable. It gives every student the opportunity to present his strong side so he is successful. The student develops his/her less good skills so that a training pedagogical balance is achieved at the end of the training.